Analysis of the Influence of Infrastructure, Costs, and Services for the Crew's PT. PELNI on Customer Satisfaction Using Principal Component Analysis (PCA) Method - Adiarsa, Hilda Emeraldo Ahmad; Huda, Mokhamad Aufal; Buana, I Gusti Ngurah Sumanta (Pusat Publikasi Ilmiah Institut Teknologi Sepuluh Nopember, 2024)
The presence of efficient port infrastructure is of utmost importance in ensuring the seamless functioning of both cargo and passenger operations. In addition to infrastructure, providing high-quality service by a ship's crew is equally important to derive from the infrastructure. Another factor to consider is whether the cost levied for services and infrastructure meets the community's expectations, as excessive costs without adequate infrastructure and services will result in dissatisfied customers. Therefore, customer satisfaction cannot only be assessed from one aspect but must be seen from various aspects, which in this study will be seen from the infrastructure, costs, and crew services. This research focuses on ships owned by PT. PELNI because this company is one of the largest in Indonesia, leading in great demand for sea transportation services. The research on infrastructure aspects, costs, and crew services includes supporting aspects to link them to customer satisfaction with PT. PELNI will be analysed using the Principal Component Analysis (PCA) method. The principal component (PC) can be utilised for feature selection and variable interpretation for data with several variables and a correlation. The results found that infrastructure (X1) can explain the factor variance of 45.309%.